Farmers’ Adoption of some Agricultural plant wastes Recycling Processes to Reduce Environmental pollution in El- Beheira Governorate in Arab Republic of Egypt - Ghozlan, Ahmed Mohamed Ali; El-Sharkawy, ElSayed Mahmoud (Journal of agricultural, environmental and veterinary sciences, 2022)
This research aimed mainly to determine the farmers’ adoption of some agricultural plant wastes recycling processes to reduce environmental pollution in the research area, and neutralizing the relationship between the degree of respondents’ adoption of some plant wastes recycling processes and the studied independent variables, also. determining The contribution of the studied independent variables in interpreting variation in the adoption level of some plant wastes recycling processes, The research was carried out in three villages in El.Beheira Government, A rand Sample 359 farmers, and the data were collected by a personal interview using questionnaire, and analyzed using the SPSS package.The main findings of this research could be summarized as follows:1- More than three-fifths of the respondents (62.4%) are characterized by a low level of adoption for some agricultural plant wastes recycling processes.2- there were statistically significant bivariate relationships at the level of 0.01 of significance between the variable of respondents ' adoption level of some agricultural plant wastes recycling processes and between variables of respondent’s age, years of experience in agricultural work, cultivated animal tenure, and the degree of contact with agricultural extension; Also there were statistically significant bivariate relationships at the level of 0.05 of significance between the variable of respondents, adoption level of some agricultural plant wastes recycling processes and between the variable of degree of dedication to agricultural work, and the degree of exposure to agricultural information sources.3- The following four independent variables followed: years of experience in agricultural work, the degree of contact with agricultural extension, cultivated animal tenure, and the degree of dedication to agricultural work, explained about 10.9% of the variances of the depended variable explained about 70.9% of the variances of the dependent Variable.4- Some recommendations were set up as a guidance in planning and implementing a suggested extension program aiming for spreading agricultural plant wastes recycling processes among farmers and encouraging them to adoption it, leading to the protection of the rural agricultural environment from pollution and achieving continuous development.
Keywords: Farmers’ Adoption; Recycling processes; Agricultural Plant Wastes; Environmental Pollution